Why edema Is a matter of the heart - Friedrich, Matthias (Circulation. Cardiovascular imaging, 2017)
I did then what I knew how to do. Now that I know better, I do better - Maya Angelou. Myocardial tissue characterization using cardiovascular magnetic resonance (CMR) has become an essential tool for diagnostic and therapeutic decision-making in patients with acute or chronic myocardial disease because it provides unique and relevant information. This is most evident in patients with suspected cardiomyopathy or myocardial involvement in systemic disease, such as amyloidosis, iron overload, or sarcoidosis. Suspected myocarditis is one of the most frequent indications for CMR scans and helps not only by confirming or refuting the disease but can also avoid other, more costly, or invasive diagnostic procedures.1 The established set of CMR criteria for the presence of myocardial inflammation, also known as the Lake Louise Criteria, yield a good diagnostic accuracy with a high negative predictive value.2 Their diagnostic targets are myocardial edema (T2-weighted images), hyperemia/capillary leak (early gadolinium enhancement), and irreversible injury (necrosis, scar; late gadolinium enhancement). Table 1 shows the likelihood of CMR criteria in various settings. View this table: Table 1. Typical Presence of CMR Findings in Patients With Different Forms and Stages of Myocarditis. See Article by von Knobelsdorff-Brenkenhoff et al. Recently, novel CMR criteria have gained significant interest, especially native T2, native T1, postcontrast T1, and the extracellular volume, the latter being calculated from native and postcontrast T1 mapping results. All these use mapping to measure myocardial proton relaxation times, which reflect tissue pathology and are less sensitive to several problems of signal intensity analyses of single images.3 Myocardial T1 has been found to be altered by …